Requirement for phosphatidylinositol 3-kinase in epidermal growth factor-induced AP-1 transactivation and transformation in JB6 P+ cells. - Huang, C (1996)
Phosphatidylinositol 3-kinase (PI 3-kinase) plays a role in a variety of biological processes, including regulation of gene expression, cell growth, and differentiation. However, little is known about its role in the cytoplasmic events involved in epidermal growth factor (EGF)-induced transduction of signals to the transcriptional machinery of the nucleus and in EGF-induced cell transformation. In this study, we examined whether PI 3-kinase is a mediator for the activation of AP-1 and neoplastic transformation by EGF in the murine epidermal cell line JB6. The results showed the following. (i) EGF not only induced a high level of PI 3-kinase activity by itself but also enhanced insulin-induced PI 3-kinase activity in JB6 P+ cells, the EGF-induced PI-3 kinase activity could be blocked by constitutive overexpression of a dominant negative P85 subunit of PI 3-kinase (deltaP85), and insulin could markedly promote EGF-induced AP-1 activity in a dose-dependent manner in JB6 P+ cells as well as promote EGF-induced JB6 P+ cell transformation. (ii) Inhibition of PI-3 kinase with wortmannin or LY294002 markedly decreased the AP-1 activity induced by insulin, EGF, or EGF and insulin in a dose-dependent manner, while wortmannin did not block UVB-induced AP-1 activity. (iii) AP-1 activation by insulin, EGF, or EGF and insulin could be completely inhibited by overexpression of deltaP85 in all the dose and time courses studied. (iv) Inhibitors of PI 3-kinase (wortmannin and LY294002) and stable overexpression of deltaP85 inhibited EGF-induced transformation but had no significant inhibitory effect on cell proliferation induced by EGF or EGF and insulin. These results demonstrate for the first time that PI 3-kinase appears to be required for EGF- or insulin-induced AP-1 transactivation and cell transformation but not cell proliferation in JB6 cells.